Consumption insurance and vulnerability to poverty: a synthesis of the evidence from Bangladesh, Ethiopia, Mali, Mexico, and Russia - Skoufias, Emmanuel; Quisumbing, Agnes R. (International Food Policy Research Institute, 2003)
This paper synthesizes the results of five studies using household panel data from Bangladesh, Ethiopia, Mali, Mexico and Russia, which examine the extent to which households are able through formal and/or informal arrangements to insure their consumption from specific economic shocks and fluctuations in their real income. Building on the recent literature of consumption smoothing and risk sharing, the degree of consumption insurance is defined by the degree to which the growth rate of household consumption covaries with the growth rate of household income. All the case studies show that food consumption is better insured than nonfood consumption from idiosyncratic shocks. Adjustments in nonfood consumption appear to act as a mechanism for partially insuring ex-post the consumption of food from the effects of income changes. Food consumption is also more likely to be covered by informal insurance arrangements at the community level than nonfood consumption. Linkages among consumption variability, the level of household consumption, the incidence of poverty, and the probability of being ever poor and the proportion of time spent in poverty are also explored for Bangladesh, Ethiopia, and Russia. All the case studies also show that households use a portfolio of risk-coping strategies, but that different types of households may have differential ability to use these strategies. In particular, poorer households may be less able to use mechanisms that rely to initial wealth as collateral. In this regard, public transfer programs may have a more redistributive effect.